2011
DOI: 10.3102/0013189x11422112
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Educational and Psychological Outcomes Between LGBTQ and Straight Students in Middle and High School

Abstract: This study finds that, compared with straight-identified youth, youth who identify as lesbian, gay, bisexual, transgender, or questioning (LGBTQ) are at greater risk of suicidal thoughts, suicide attempts, victimization by peers, and elevated levels of unexcused absences from school. Results disaggregated by LGBTQ subgroups reveal heterogeneity within the broad LGBTQ group, with bisexual youth appearing to be particularly at risk. Also, although the risk gaps in school belongingness and unexcused absences are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(195 citation statements)
references
References 42 publications
7
181
2
5
Order By: Relevance
“…More specifically, they found in most surveys that one-fourth to one-third of LGB adolescents reported suicide attempts, compared to one-tenth or less for their heterosexual peers. This overrepresentation of sexual minority youth in regards to suicidal behaviour has been observed elsewhere in the United States (Hatzenbuehler, 2011;Robinson, & Espelage, 2011) as well as internationally (Värnik et al, 2009). …”
Section: Review Of the Literaturesupporting
confidence: 57%
“…More specifically, they found in most surveys that one-fourth to one-third of LGB adolescents reported suicide attempts, compared to one-tenth or less for their heterosexual peers. This overrepresentation of sexual minority youth in regards to suicidal behaviour has been observed elsewhere in the United States (Hatzenbuehler, 2011;Robinson, & Espelage, 2011) as well as internationally (Värnik et al, 2009). …”
Section: Review Of the Literaturesupporting
confidence: 57%
“…Other studies (Collier et al, 2013;Robinson and Espelage, 2011) had already shown that bisexual youth victims of cyberbullying or homophobic bullying were more likely to develop suicidal ideations. In our study, prevalences are roughly equivalent for cyberbullying, but higher prevalence is found regarding suicidal ideations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite research showing that bisexual youths maintain elevated social and emotional difficulties compared to gay or lesbian youth (Robinson & Espelage, 2011), more recent qualitative research helps understand the lessening of biphobia in contemporary cultures.…”
Section: Decreasing Homophobia and Biphobiamentioning
confidence: 99%
“…Anderson, McCormack & Ripley, 2014;McCormack, 2012b;Morris, 2014), as well as research that focuses on negative experiences (e.g. Robinson & Espelage, 2011). In other words, research finding a lessening of negative experiences does not homogenize sexual minority experience, and the turn toward this diversity has not resulted in an absence of research documenting negative experiences.…”
mentioning
confidence: 99%